Factors Affecting Behavioral Intention Towards E-Wallet–A Case Study Among Foundation Students - Suppiah, Sharvina; Vong, Siew Chie; Mohamad Sahide, Aisyah; Frederick Liwa, Clarrissa Evitha; Amurad, Ummi Syahirah Husna; Md Yusof, Zahayu; Misiran, Masnita (CLM Publishing Resources, 2024)
E-Wallet is an electronic financial transaction made online via mobile devices. The development of technologies has promoted the higher usage of this method among users around the world. This study aims to investigate the factors affecting behavioral intention among Foundation Studies students towards the usage of E-Wallet. There are 150 students involved in this study. Descriptive statistics were adopted to achieve the research objective. The finding shows that 87% of the respondents preferred to used e-wallets in their daily life activities and majority of them are female students. Students from urban area are more familiar with the E-Wallet and promotion of the benefits of E-Wallet should be conducted in the rural area